Do Advanced Therapies Have a Future in the Low- and Middle-Income Countries - The Case of Bulgaria, Romania, and Poland - Kamusheva, Maria; Turcu-Stiolica, Adina; Gierczyński, Jakub; Subtirelu, Mihaela-Simona; Czech, Marcin; Petrova, Guenka (Frontiers in Public Health, 2021)
Introduction: The significant therapeutic potential of the advanced therapies (ATs) has predetermined the increased interests in their development mainly in the context of rare diseases most of which are genetically determined. However, there are still many challenges in front of the health insurance funds related to the cost-effectiveness and budget impact issues of these therapies. Our aim was to review and analyze the potential of low- and middle-income countries for health technology assessment (HTA) of advanced therapies focusing on Bulgaria, Romania and Poland as reference countries. A literature review of the existing good practices related to HTA of advanced therapies across the world and comparison with the national reality were performed. A list of challenges and issues from the point of view of the payer institution of all analyzed countries was performed. Pilot recommendations on how to overcome the barriers were created based on the existing practices and the potential of the national system. Discussion: 15 out of 80 articles identified in PubMed were found as applicable to the study scope as most of them were published in the period 2019–2021. Undoubtedly, the main challenges correspond to the high treatment costs, the uncertainty in clinical effectiveness, and poor HTA methodological approaches applicable for ATs worldwide. The issues identified for low and middle-income countries are similar having as well the lack of enough qualified health economists for the purposes of assessment and appraisal of HTA dossiers of the advanced therapies, lack of adequate existing separate financial programs for those therapies, and not preparedness of the health system and the society as a whole for such therapies. Conclusions: Despite the difficulties and challenges, the advanced therapies can be defined as a futuristic therapy for which great discoveries are yet to come. Therefore, each country should consider the implementation of reliable and nationally oriented programs for HTA and adequate financial coverage of these therapies.